Avifauna, Alto do Palácio, Serra do Cipó National Park, state of Minas Gerais, southeastern Brazil - Rodrigues, Marcos; Freitas, Guilherme H.S.; Costa, Lilian M.; Dias, Daniel F.; Varela, Mariane L. M.; Rodrigues, Licléia C. (Check list (Luís Felipe Toledo), 2011)
We surveyed the avifauna of Alto do Palácio, Serra do Cipó National Park, Minas Gerais state, Brazil. The park lies in the southern Espinhaço range, a significant biogeographical barrier that separates the forest areas of the Atlantic Forest on its eastern slope and the savanna-like vegetation of the Cerrado to its western slope. Representative habitats include open grasslands, with patches of rocky outcrops and woodlands. We recorded 151 species between 2007 and 2010. Most species occurred in woodlands, with the minority in rocky outcrops, eleven species are of conservation concern, nineteen are endemic to the Atlantic Forest, three to Cerrado, and four to the southeastern Brazilian mountaintops, two of which are restricted to campos rupestres of the Espinhaço range. Our results corroborate that the campos rupestres of the Espinhaço range are not only associated with the Cerrado biome, but harbor species associated with both surrounding biomes (Cerrado and Atlantic Forest) and to the mountaintops of southeastern Brazil, supporting the uniqueness of this vegetation type.